The Role of Social Interactions in Learning Ethno-National IdentityThe Case of the Divided Island of Cyprus - Christos Anagiotos (Adult Education Research Conference, 2015)
Cyprus is a divided island as a result of nationalist conflict between the Greek-Cypriot and the Turkish-Cypriot communities, which lived apart from 1974 until 2003. Using narrative analysis this paper examines how social interactions outside Cyprus influence ethno-national identity learning of young Greek-Cypriot and Turkish-Cypriot adults.
Keywords: national ethnic identity; informal learning; social interactions; Cyprus